Interaction of the Onset of Spring and Elevated Atmospheric CO(2) on Ragweed (Ambrosia artemisiifolia L.) Pollen Production - Rogers, Christine A. (National Institute of Environmental Health Sciences, 2006)
Increasing atmospheric carbon dioxide is responsible for climate changes that are having widespread effects on biological systems. One of the clearest changes is earlier onset of spring and lengthening of the growing season. We designed the present study to examine the interactive effects of timing of dormancy release of seeds with low and high atmospheric CO(2) on biomass, reproduction, and phenology in ragweed plants (Ambrosia artemisiifolia L.), which produce highly allergenic pollen. We released ragweed seeds from dormancy at three 15-day intervals and grew plants in climate-controlled glasshouses at either ambient or 700-ppm CO(2) concentrations, placing open-top bags over inflorescences to capture pollen. Measurements of plant height and weight; inflorescence number, weight, and length; and days to anthesis and anthesis date were made on each plant, and whole-plant pollen productivity was estimated from an allometric-based model. Timing and CO(2) interacted to influence pollen production. At ambient CO(2) levels, the earlier cohort acquired a greater biomass, a higher average weight per inflorescence, and a larger number of inflorescences; flowered earlier; and had 54.8% greater pollen production than did the latest cohort. At high CO(2) levels, plants showed greater biomass and reproductive effort compared with those in ambient CO(2) but only for later cohorts. In the early cohort, pollen production was similar under ambient and high CO(2), but in the middle and late cohorts, high CO(2) increased pollen production by 32% and 55%, respectively, compared with ambient CO(2) levels. Overall, ragweed pollen production can be expected to increase significantly under predicted future climate conditions.